Translation of Culture-Bound Items from Arabic into English - Mohamed Sidi Mohamed Sidi Mahmoud (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2023)
This article aims to examine the procedures and strategies followed in the translation of the Arabic Mauritanian novel into English. It explores the difficulties encountered in the rendition of the cultural forms and units such as metaphors, similes, idioms, and culture specific terms from the ST into the TT. For solving the semantic and lexical gaps in Arabic/English literary translation, this dissertation highlights a practical framework that is built on two criteria: consideration of the cultural terms of the source culture and respect for the target language system. To do so, I make use of foreignization strategies including literal translation and borrowing with footnotes to transfer the entire cultural content of the ST. For handling linguistic gaps, I make use of domestication strategies. The study has found that the foreignization strategy in literary translation appears to be more faithful in the rendition of the source culture into the target one. However, it seems inadequate when it comes to the translation of linguistic features of the novel; hence, the domestication strategy proves to be more appropriate in the case of translating lexical, syntactic, semantic and stylistic features from Arabic into English. The obtained findings point out that literary translation is not simply technical renditions of the ST lexemes into their counterparts in the TT, but rather requires the translator to offer explanations and comments to convey the entire meaning of the cultural items embedded in the ST to the TRs.